Income-related inequalities in cardiovascular disease from mid-life to old age in a Northern Swedish cohort: A decomposition analysis. (January 2016) - Mosquera, Paola A.; San Sebastian, Miguel; Waenerlund, Anna-Karin; Ivarsson, Anneli; Weinehall, Lars; Gustafsson, Per E.
Abstract: While the social determinants of cardiovascular disease (CVD) are fairly well-known, the determinants of socioeconomic inequalities in CVD are scarcely studied and almost completely based on cross-sectional designs in which the changing circumstances across the life course are not taken into account. The present study seeks to incorporate a life course approach to the social determinants of socioeconomic inequalities in CVD. The specific aims were to 1) examine how income-related inequalities in CVD change over two decades of the mid-late life course, and 2) identify the key social determinants of the inequalities at each time period. The cohort (N = 44, 039) comprised all individuals aged 40–60 years in 1990 who during 1990–2010 were enrolled in the county-wide preventive effort :"Västerbotten Intervention Program" (VIP). The cohort was followed over these two decades by Swedish population register data linked within the Umeå SIMSAM Lab micro data infrastructure. First-time hospitalization for CVD and mean earned income were used to calculate the concentration index (C) during four periods of 5–6 years. The C for each period was decomposed by sociodemographic factors, using Wagstaff-type decomposition analysis. Results suggest that inequalities in CVD increase gradually from mid-life to old age; from initially non-significant to particularly marked among the elderly. The decomposition showed that, from middle to old age, educational and employment inequalities underwent a transition from initially dominant to a moderate role in explaining the health inequalities, coupled with an increasing importance of age and a stable role of income. In conclusion, the study illustrates the need for incorporating a dynamic life course perspective into research, policy and practice concerned with equity in health. Highlights: Income inequalities in CVD increased gradually from mid-life to old age. The key factors explaining CVD inequalities underwent life-course transitions. Labour market factors successively gave way to age as a central determinant. Income inequalities remained a persistently key determinant across aging. A joint equity lens and life course approach may be needed to tackle inequities.